The relationship between food type, nutritional status and iron intake with the incidence of anemia in pregnant women at the Sukamakmur health center - Novriyana, Ima; Sari, Yuni; Yushida , Yushida; Zahara, Evi; Gustiana, Gustiana (Journal of Midwifery and Nursing, 2025)
Anemia in pregnant women is one of the most common public health problems, mainly caused by iron deficiency. This condition can cause serious complications for both mother and fetus. The purpose of this study was to determine the relationship between food type, nutritional status, and iron intake with the incidence of anemia in pregnant women at the Sukamakmur Health Center. This study used a quantitative approach with an analytical survey design and a cross-sectional method. The sample amounted to 56 pregnant women in the third trimester which were taken using the total sampling technique. This study uses a multivariate approach to understand how these three independent factors (food type, nutritional status, and iron intake) together influence the incidence of anemia in pregnant women in their third trimester. Data collection was carried out through questionnaires and analyzed with the Spearman test.  There was a significant negative association between food types and the incidence of anemia (r = -0.527; p < 0.05). Iron intake was also significantly negatively associated with the incidence of anemia (r = -0.311; p < 0.05). However, there was no significant association between nutritional status and the incidence of anemia (r = 0.130; p = 0.341). Diversity of food types and iron intake contribute to a decrease in the incidence of anemia in pregnant women. However, general nutritional status such as BMI did not show a significant relationship. Continuous education is needed for pregnant women regarding the consumption of nutritious foods, especially foods high in iron.